Effect of nitrogen levels and weed control methods on productivity and profitability of rice (Oryza sativa L.) - Vipin Kumar Shukla; H.S. Kushwaha; R.K.Tiwari (Annals of Agricultural Research, 2022)
A field experiment was carried out during rainy seasons of 2015-16 and 2016-17 at the Vivekanand Anusandhan Kendra Ram Krishna Puram, Gudahar, Rewa (M.P.) to study the effect of N-levels and weed control methods on growth, productivity and economics of rice. The application of 125 kg N/ha produced significantly higher growth parameters viz. plant height and no. of tiller/plant; higher of grain yield (22.58 q/ha), greater net returns (`24889/ha) and B:C ratio (2.04) from transplanted rice var. PS-5. The weed control treatment W6 (HW 20 & 40 DAS) followed by butachlor - 2 HW recorded a higher growth parameters viz plant height and tillers/plant, and higher grain yield (25.44 and 23.86 q/ha, respectively). Net returns and B:C ratio were greater for 2 HW (`29470/ha; 2.14) and butachlor - 2,4-D (`25234; 2.15). The best substitute for 2 HW with or without butachlor was butachlor - 2,4-D 0.80 kg/ha or butachlor - bispyribac sodium (20 g/ha) which equally yielded 20.57 to 21.82 q/ha rice grain and resulted to higher net income (`22531 to 25334/ha).